A Model of Information Technology Adoption Readiness among SMEs In Java Island - Asrul, Sani (2023)
The development of information technology in Indonesia has advanced in tandem with its increased usage in the industrial and SMEs sectors. Implementation of IT has become a necessity in order to enhance the quality of these sectors. Institutionally, this is essential to ensure affordable access and quality when it comes to managing performance. However, in reality, the use of IT among the SMEs is still considered low and this is said due to the readiness of users in IT utilization. To examine these phenomena, this study was conducted to determine the level of readiness of users in the SMEs sector towards the utilization of information technology by adopting a pre-existing model. The objective of the research was to evaluate and assess the factors that impact the level of readiness in IT utilization among SMEs on Java Island. The research model was built by adopting, combining, and adapting the technology readiness and adoption models with regards to selected theories. Methodologically, a quantitative approach was implemented throughout the research. The research took a survey of SMEs in Indonesia that were scattered across various points of the Java Island. Samples were taken from SMEs that had implemented IT in their companies, decided by the purposive sampling method and reaching 407 respondents. Valid surveys of the results response were then analyzed using Partial Least Squares (PLS-SEM). The findings of the research prove that the use of IT in SMEs must be accompanied by a degree of technology readiness as it has an influence on the effects of its utilization. This research also produces a new model, namely the modified adoption model of information technology utilization for SMEs on Java Island.